2005
DOI: 10.1001/jama.294.9.1025
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Performance of Residents After Heavy Night Call vs After Alcohol Ingestion

Abstract: Post-call performance impairment during a heavy call rotation is comparable with impairment associated with a 0.04 to 0.05 g% blood alcohol concentration during a light call rotation, as measured by sustained attention, vigilance, and simulated driving tasks. Residents' ability to judge this impairment may be limited and task-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
206
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(225 citation statements)
references
References 62 publications
8
206
1
10
Order By: Relevance
“…The number of staff required will be calculated according to the number of beds in the unit, number of shifts per day, desired occupancy rate, extra manpower for holidays and illness, number of days each professional is working per week, and the level of care and as a function of clinical, research, and teaching workload. Extended work shifts have been shown to negatively impact the safety of patients as well as medical staff [18][19][20]. The number of full time equivalent (FTE) physicians qualified in intensive care medicine per six to eight intensive care beds (at level of care II, see section ''Activity Criteria'') can be calculated (according to the European working hours directives) with the formula provided in paragraph 9 of the ESM [21].…”
Section: Medical Staffingmentioning
confidence: 99%
“…The number of staff required will be calculated according to the number of beds in the unit, number of shifts per day, desired occupancy rate, extra manpower for holidays and illness, number of days each professional is working per week, and the level of care and as a function of clinical, research, and teaching workload. Extended work shifts have been shown to negatively impact the safety of patients as well as medical staff [18][19][20]. The number of full time equivalent (FTE) physicians qualified in intensive care medicine per six to eight intensive care beds (at level of care II, see section ''Activity Criteria'') can be calculated (according to the European working hours directives) with the formula provided in paragraph 9 of the ESM [21].…”
Section: Medical Staffingmentioning
confidence: 99%
“…Also, busy nights on call have been shown to cause neurobehavioral changes in residents equivalent to alcohol levels above the Canadian legal limit. 14,15 Work hour reforms and increased scrutiny of resident physicians have also been influenced by increased public awareness of the issue and by high profile legal cases, such as the Libby Zion case. [16][17][18] Consequently, national bodies in many countries have recently instituted legislation and guidelines to reduce sleepiness and fatigue among physicians by limiting working hours and on-call coverage.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is the fact that these studies utilize a wide variety of methods in small samples making it difficult to validate results. Several studies have been carried out through the application of psychomotor tests applied to a doctor after sleep deprivation and showed decreased reaction time, increased response time variability and increase drowsiness 10,13,14 Pilcher et al 15 published a meta-analysis that found that mood is more affected by sleep deprivation than either cognitive or motor performance and that partial sleep deprivation has a more profound effect on functioning than either longterm or short-term sleep deprivation. Ayas et al 16 showed a higher incidence of medical errors including wrong decision making and needlestick incidents.…”
mentioning
confidence: 99%